Towards an essential knowledge transfer process model in the flood management domain - Yahya H.B.; Ahmad M.N.; Mohamad R. (Asian Research Publishing Network, 2023)
The study of knowledge transfer is becoming important in many areas such as small-medium enterprises, higher education, health management and disaster management. Our study focuses on the process of knowledge transfer in the flood management domain in Malaysia. Currently, there is a lack of standard practice in terms of transferring knowledge between entities in this domain. Thus, based on a review of the literature, we propose the conceptual model of a knowledge transfer process in the flood management domain. The proposed model is a preliminary work which will be evaluated in the next phase. 2006-2015 Asian Research Publishing Network (ARPN).